A familia camponesa e o trabalho na infância: uma incursão bibliográfica - BRITO, Simone Nunes de (2022)
This study seeks to elucidate the disputes between dominant work and ontological work, since when human evolution is portrayed in a historical panorama there is a clash between domination and liberation, therefore, one corrupts the being while the other socializes one's own. It is with this perception of primary socialization that the peasant family assumes the responsibility of educating by inserting ontological work in their offices. Considering this review, it is concluded that the domineering work establishes the depreciation of reality and the strangeness among individuals, unlike the formation work in childhood, which has the capacity to socialize and educate the child, but also prepare it for a recognized reality. This research was based on the qualitative exemplary calculation, which was carried out from a bibliographic review, characteristic of a descriptive research.